The Relationship between Self-Efficacy and Self-Regulated Learning on Teenagers - Gressy Rahma Jirandha; Mustika Candra Nugraha; Salsabil Firdauz; Shada Noorfathya Achmad (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
Educational demands make adolescents must have independence in learning. This cannot be separated from self-efficacy and self-regulated learning which play an important role in overcoming the demands of education in an era full of competence and pressure. In the context of learning, self-efficacy is very important because it can affect one's motivation, effort, and performance in learning. Self-regulation is one of the factors that plays an important role as one of supporting the success of adolescents in learning. Therefore, self-efficacy and self-regulated learning influence each other and have a relationship. This research to see the relationship between self-efficacy and self-regulated learning on teenegers. This research uses the literature study method in which the researcher explores studies that have been conducted by other people on a particular topic or issue and then analyses the data.